先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 18:40:58
先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3先化简,再求值(3x/x-2+x
先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3
先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3
先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3
[3x/(x-2)+x/(x+2)]/[x/(x²-4)]
={[3x(x+2)+x(x-2)]/(x²-4)}/[x/(x²-4)]
=[(4x²+4x)/(x²-4)]/[x/(x²-4)]
=[4x(x+1)/(x²-4)]/[x/(x²-4)]
=4x+4
=4×(-3)+4
=-8
原式=x(3x+6+x-2)/(x-2)(x+2)*(x+2)(x-2)/x=4x+4
∴当x=-3时,原式=-12+4=-8
先化简,再求值:(x-2/x-x+2/x)/x-2/4x,x=2011
先化简,再求值:(x+2)(x-2)-x(x-3),其中x=三分之一
先化简,再求值(1)(x-1)(x+4)-(x-3)(x+2),其中x=三分之一
先化简,再求值:(2-x/x^2+x)/(x^2-3x/x^2+2x+1)x(9-x^2/4-2x),其中x=-2
先化简,再求值:(x-1)(x-2)-3x(x+3)+2(x+2)(x-1),其中x=三分之一
先化简,再求值:(x-1)(x-2)-3x(x+3)+2(x+2)(x-1),其中x=三分之一
先化简,再求值:(3x/x-1-x/x+1)×x^2-1/x,其中,x=(根号2)-2
先化简,再求值:x(x-1)+2x(x+1)-(3x-1)(2x-5),其中x=2
先化简,再求值(3x/x-2+x/x+2)/(x/x²-4),其中x=-3
先化简,再求值:5x(x的平方+2x+1)-x(x-4)(5x-3),x等于1
先化简,再求值:x^3+2x^2+x/x^2+2x-8除以(x/x-2 × x+1/x+4),其中x=负5/4
先化简,再求值:(x+3)²+(2+x)(2-x),其中x=-2
先化简,再求值:x+3/x+2除以(x-2-[5/x+2})
x^2+(4x-3x^2)-(5x-6x^2)-2,x=1/2,先化简,再求值.
先化简,再求值:(x^2/x-3-9/x-3)*1/x^2+3x,其中x=1/3
先化简,再求值:(2x-1)^2+(x+2)(x-2)-4x(x-1),其中x=根号3
先化简,再求值:(1+x)/(x²+x-2)÷[(x-2)+(3)/(x+2)],其中x=1/2
{2x+3}{x-1}-{2x+1}2+4x{x+1} ,其中x=-2 {先化简,再求值}